Shuttle balance between lithiophilic functionalities substituted on conjugated polymers to improve lithium-ion diffusion and cycling stability of batteries - Kargude, Radhakisan; Javaregowda, Bharathkumar H.; Palani, Sathishkumar; Singh, Anup K.; Krishnamoorthy, Kothandam (Macromolecules, 2024)
Herein, we report the design and synthesis of i-Indigo and trans-1,2-di(2-thienyl)ethylene (TVT) comprising copolymers with various side chains that are used as anode-cum-binder in Li-ion batteries. The TVT disrupts the crystallinity, and the i-Indigo renders the handle for unsymmetrical substitution. Polymer P1 comprises alkyl chains on i-Indigo, whereas P2 comprises an alkyl chain and a chain with a urethane moiety as another side chain. Polymer P3 comprises i-Indigo with a urethane moiety and triethylene glycol as side chains. The i-Indigo in P4 is substituted with triethylene glycol and alkyl chains as side chains. These polymers were found to be amorphous with pi-pi stacking due to the extremely small torsional angle imparted by TVT moieties. All of these polymers showed comparable specific capacity while used as an anode in Li-ion batteries due to the presence of a common conjugated backbone. However, the battery metrics varied significantly while the current density of the batteries varied between 0.1 and 2.0 A g(-1). P1 and P2 showed a very close recovery of specific capacity at 0.1 A g(-1) before and after various current densities. However, polymers P3 and P4 did not recover from the specific capacity fading due to the presence of triethylene glycol side chain that degraded. Polymer P2 with an alkyl side chain and a chain with a urethane moiety showed stable performance over 2000 charge-discharge cycles. Contrary to this, the stability of polymers with triethylene glycol side chains decreased over 2000 charge-discharge cycles. Polymer P2 with a urethane side chain also showed improved Li-ion diffusion because the urethane moiety facilitated better Li-ion transport.

Synergistic effect of lactam and pyridine nitrogen on polysulfide chemisorption and electrocatalysis in lithium sulfur batteries - Javaregowda, Bharathkumar H.; Kargude, Radhakisan; Birajdar, Sarika; Shivankar, Bhavana; Krishnamurty, Sailaja; Jones, Lathe A.; Caruso, Rachel A.; Krishnamoorthy, Kothandam (ACS APPLIED MATERIALS & INTERFACES, 2024)
Keywords: Li-S battery; phenyl-diketopyrrolopyrrole; pyridine-diketopyrrolopyrrole